Ethnically Sensitive Rhinoplasty - Deeb, Robert (Facial Plastic Surgery, 2023)
Ethnically sensitive rhinoplasty presents a unique challenge. There are a large number of variations in skin tone, skin thickness, and structural deformities, which require a high degree of thoughtfulness and planning. A thorough history and physical examination are the cornerstone to achieving a good result. An open and honest discussion is necessary to fully understand the patient's goals. The surgeon should clearly define which goals are achievable and which are not. An individualized approach with special consideration toward maintaining ethnic heritage is imperative. Conservative techniques will help achieve a natural, balanced outcome and will allow for preservation of nasal function.
Keywords: ethnic rhinoplasty; nasal surgery; cosmetic rhinoplasty